(untitled) (Altre Modernità, 2024)
The non-recognition of perinatal bereavement in society leads parents to an isolated condition that may hinder their psychological adjustment after the loss (Layne; Markin and Zilcha-Mano). Improving bereaved parents’ experiences of communication in healthcare practice thus seems to be crucial to lessening the risk of dysfunctional grief. This paper presents a research project on the topic of perinatal death, “Words Fail Me”: Naming the Unnamable (PERINAT), funded by the French National Agency for Research (2023-2027). By focusing on the metaphorical constructions used by bereaved parents in their narratives of perinatal death, PERINAT seeks to improve the communication experience of the bereaved by furthering health care practitioners’ understanding of this grief. The study is conducted by means of a dataset collected in 2022-23 from interviews with a hundred bereaved parents in France. The preliminary findings of this ongoing project are meant to be used to inform and improve the support offered by health care providers who are likely to come across a bereaved parent in their professional capacity. More specifically, from a perspective of narrative medicine, this contribution seeks to explore what the study of metaphor can potentially offer to the development of narrative competence in the training of health professionals. By developing higher awareness of bereaved parents’ narrative, more specifically of their use of figurative language, practitioners can make sense of parents’ needs and emotional responses to their experience of loss in order to ease it. As Norwood (122) has it, metaphor, like poetry, “can make unknown known and the unspeakable speakable”. This is also in line with the most recent promotion of a relationship-centered and patient-centred notion of care (Bensing; Pluut).